PENGARUH KUALITAS LAYANAN DAN KEMUDAHAN PENGGUNAAN APLIKASI MOBILE JAMINAN KESEHATAN NASIONAL (JKN) TERHADAP KEPUASAN MASYARAKAT PESERTA BPJS KESEHATAN DI KOTA BEKASI - Kurnianti, Intan; Vitisia, Vita (Jurnal Ilmu Administrasi Publik, 2025)
This study aimed to determine whether the quality of service and ease of use of the JKN Mobile Application affect the satisfaction of BPJS Health participants in the Bekasi Region, both partial and simultaneous effects. This study used a quantitative descriptive method. The study population were all BPJS Health participants in Bekasi, which numbered 2,487,627 million people in April 2024. The sampling technique used was Accidental Sampling with calculations using the Slovin formula resulting in a sample size of 100 respondents. The data used in this study used a questionnaire instrument distributed via online or searching directly to the research location. This study used quantitative primary data with several test stages carried out, namely validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination, partial test (T test) and simultaneous test (T test). The results of the t test (X1) T score -3.616> T table 1.660 with a significance value smaller than the significant level (0.000 <0.05) Then H0 is rejected and H1 is accepted, which means that the Service Quality variable has a significant effect on Community Satisfaction. The T test results (X2) T score 7.914> T table 1.660 with a significance value smaller than the significant level (0.000 <0.05). Then H0 is rejected and H1 is accepted, which means that the Ease of Use variable has a significant effect on Service Quality In addition, the results of the F test (Y) T table of 3.09. Then the T score value of 40.95 is greater than the F table value of 3.09 with a significance of 0.000 which is smaller than 0.05. With the Quality of Service and Ease of Use in the JKN Mobile Application provided simultaneously, it will increase public satisfaction as BPJS Health participants, especially in Bekasi